Food price policy in an era of market instability : a political economy analysis - Pinstrup-Andersen, Per (Oxford : Oxford University Press, 2015)
Food price volatility is one of the major challenges facing current and future global food systems. This book analyses how and why governments responded as they did to the global food crisis of 2007-09 and what their decisions can teach us about policy interventions.
Specialized.
Description based on online resource; title from home page (viewed on December 17, 2014).
Keywords: Food prices -- Government policy; Food supply -- Government policy; Food supply -- History -- 21st century